A Comprehensive Systematic Review of The Relationship between Poverty Status and Access to Tuberculosis Treatment in Developing Countries - Harlina Hi M Konoras; Muhammad Irsan; Brian Enrique Fritzgerald (The Indonesian Journal of General Medicine, 2026)
Introduction: Tuberculosis (TB) remains a major global health challenge, disproportionately affecting populations in low- and middle-income countries (LMICs). Poverty is a fundamental social determinant that intersects with and exacerbates barriers to TB care, from diagnosis through treatment completion. Understanding the multifaceted relationship between poverty status and access to TB treatment is critical for designing equitable and effective interventions to end the TB epidemic (Teo et al., 2020; Tanimura et al., 2014). Methods: This comprehensive systematic review synthesized evidence from 80 studies examining the relationship between poverty and TB treatment access in developing countries. A rigorous screening process was employed, focusing on studies with TB patients in LMICs that quantitatively assessed economic factors as exposures and treatment access as an outcome. Data extraction followed a structured protocol covering study context, poverty definitions, treatment access measures, financial and non-financial barriers, treatment outcomes, and tested interventions. Results: The evidence consistently demonstrates a strong negative association between poverty and TB treatment access. A significant proportion of TB patients face catastrophic health expenditures, with rates reaching 43% overall, 80% for drug-resistant TB, and 81% for HIV-coinfected patients (Ghazy et al., 2022; Ghazy et al., 2021). Indirect costs, primarily income loss, constitute approximately 60% of the total financial burden. Non-financial barriers, including geographic distance, stigma, and structural healthcare system limitations, further impede access. Poverty is associated with longer diagnosis and treatment delays, with patient delays averaging 28 days in low-income countries compared to 10 days in upper-middle-income countries (Teo et al., 2021). Effective interventions include cash transfers (OR 1.77 for positive clinical outcomes), food support, decentralized diagnostics, and community-based care models (Richterman et al., 2018; Filho, 2009; Assebe et al., 2025). Discussion: The relationship between poverty and TB treatment access is complex and mediated through multiple pathways. The heterogeneity in findings can be explained by contextual factors such as national economic development, drug resistance status, and case-finding strategies. The dominance of indirect costs highlights the insufficiency of policies focusing solely on eliminating direct medical fees. Multi-component, pro-poor interventions that address financial, geographic, and social barriers simultaneously show the greatest promise for improving equity in TB care. Conclusion: Poverty is a powerful driver of inequitable access to TB treatment in developing countries, leading to catastrophic costs, treatment delays, and poorer outcomes. To achieve global TB targets, programs must move beyond medical-focused models and integrate comprehensive social protection, poverty-sensitive service delivery innovations, and active case-finding strategies tailored to the needs of the most vulnerable populations. Future research should employ standardized poverty measurements and robust designs to evaluate the cost-effectiveness of integrated, pro-poor TB interventions.